Collision of power : [large type] Trump, Bezos, and The Washington Post - Baron, Martin, 1954- (Thorndike Press large print nonfiction series., 2023)
"Marty Baron took charge of The Washington Post newsroom in 2013. Seven months into his new job, Baron received explosive news: Jeff Bezos, the founder of Amazon, would buy the Post. Just over two years later, Donald Trump won the presidency. In the face of Trump's unceasing attacks, Baron steadfastly managed the Post's newsroom, during a period of rapidly changing societal dynamics. In Collision of Power, Baron recounts this with the tenacity of a reporter and the sure hand of an experienced editor. The result is elegant exploration of the nature of power in the 21st century"--